Serum Zinc Levels in Women with Polycystic Ovarian Syndrome are Lower as Compared to Those without Polycystic Ovarian Syndrome: A Cohort Study - Swati Dhar; Reena Yadav; Akash Tomar (Journal of Human Reproductive Sciences)
Background: Zinc is an essential micronutrient, a vital stabiliser and a cofactor in many enzymes such as superoxide dismutase and phospholipase C and also acts as an antioxidant by protecting the sulfhydryl groups of different proteins and enzymes against free radicals. It is unclear if serum zinc levels are correlated with polycystic ovary syndrome (PCOS) and its pathophysiology, although relation between diabetes and insulin resistance has been established. Aims: This study aimed to investigate circulating serum zinc levels in PCOS subjects compared with non-PCOS subjects. Settings and Design: In this cohort study, PCOS subjects were compared with normal subjects aged between 18 and 35. Materials and Methods: All the included subjects underwent measurement of anthropometric parameters, fasting insulin, luteinising hormone, follicle-stimulating hormone, thyroid-stimulating hormone, prolactin, progesterone, oestrogen and serum zinc levels. These values were taken on days 2–5 of the menstrual cycle. Statistical Analysis Used: Univariate analysis and linear regression were performed for serum zinc levels and fasting insulin levels in PCOS subjects and non-PCOS subjects using SPSS (version 21) and Microsoft Excel (2019). Results: Serum zinc levels in the PCOS group were lower than in the control group (P = 0.012). Fasting insulin levels in the PCOS group were higher than in non-PCOS subjects (P = 0.001). We found a negative correlation between zinc and fasting insulin (r = −0.580, P < 0.0001) in the normal group and (r = −0.332, P = 0.019) in the PCOS group. A positive correlation was found between body mass index (BMI) and fasting insulin levels in both the PCOS group (r = 0.227, P = 0.112) and normals (r = 0.612, P < 0.0001). A negative statistically significant correlation between BMI and zinc in both the PCOS group (r = −0.378, P = 0.007) and the non-PCOS group (r = −0.7452, P < 0.0001) was seen. Conclusion: The data suggest that serum zinc levels were found to be lower in PCOS subjects as compared to normal controls and evaluation of these levels may indicate that zinc has a vital role in PCOS pathophysiology.